The parametrically adjusted hyperspectral data compression algorithm based on wavelet decomposition - D. Y. Pertsau; A. A. Doudkin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The parametrically adjusted hyperspectral data compression algorithm based on wavelet decomposition is presented. Data stream compression throughput assessment depending on wavelet decomposition level is carried out, the overall performance of the presented algorithm is estimated.